2022
DOI: 10.1021/acscatal.2c00755
|View full text |Cite
|
Sign up to set email alerts
|

C60 Adsorbed on TiO2 Drives Dark Generation of Hydroxyl Radicals

Abstract: The photocatalytic effect of TiO2 has attracted a great deal of interest due to its many applications, especially water splitting. However, the wide band gap of TiO2 limits its efficiency as a photocatalyst in practical applications. Considerable efforts have so far been made to extend the spectral response to the visible light region. Here, we report the dark catalysis of water dissociation on a TiO2(110) surface. C60 molecules “decorated” this surface and acted as molecular electron acceptors. This adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The reasons for the appearance of DMPO–˙OH ESR signals under dark conditions are that the Ni 5 P 4 /TiO 2 /C NFs themselves are inherently rich in hydroxyl radicals, and the oxidation process of water on the surface of Ni 5 P 4 /TiO 2 /C NFs consumes surface holes, resulting in the production of a small amount of free radicals. 37 In order to further verify the effect of different active groups, quenching agents were used to inhibit the catalytic activity of active species, and when the hydrogen evolution efficiency decreases, it can be confirmed that the active species participate in the hydrogen evolution reaction. In this paper, isopropanol (IPA), ethylene diamine tetraacetic acid (EDTA) and benzoquinone (BQ) were used as scavengers for photocatalysis of hydroxyl radicals (˙OH), hole radicals (h + ) and superoxide radicals (˙O 2 − ), respectively (the dosage of the inhibitor was 1 mmol).…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for the appearance of DMPO–˙OH ESR signals under dark conditions are that the Ni 5 P 4 /TiO 2 /C NFs themselves are inherently rich in hydroxyl radicals, and the oxidation process of water on the surface of Ni 5 P 4 /TiO 2 /C NFs consumes surface holes, resulting in the production of a small amount of free radicals. 37 In order to further verify the effect of different active groups, quenching agents were used to inhibit the catalytic activity of active species, and when the hydrogen evolution efficiency decreases, it can be confirmed that the active species participate in the hydrogen evolution reaction. In this paper, isopropanol (IPA), ethylene diamine tetraacetic acid (EDTA) and benzoquinone (BQ) were used as scavengers for photocatalysis of hydroxyl radicals (˙OH), hole radicals (h + ) and superoxide radicals (˙O 2 − ), respectively (the dosage of the inhibitor was 1 mmol).…”
Section: Resultsmentioning
confidence: 99%
“…15–22 Among them, the in situ formation of ˙OH is of great significance for environmental remediation, which is due to its strong oxidation capacity. 23–25 However, a one-step single-electron oxygen reduction reaction (ORR) is easy to achieve, resulting in ˙O 2 − radicals as the main ROS. Considering that the photocatalytic properties of these charge transfer processes are related to the lifetime and concentration of the carriers that can reach the catalyst surface, great efforts have been made in the separation of photoinduced electron–hole pairs, especially in nanostructure design and band structure specifications.…”
Section: Introductionmentioning
confidence: 99%